Grounded Theory for Implementation of Labor Policy Women Disability Research - Audiyah, Nailatul Muinah; Putra, Fadillah; Wike, Wike (The Center for Disability Studies and Services Brawijaya University, 2019)
Implementation of employment policies for women with disabilities using grounded theory, because researchers assume that the method, can reveal the problem in this study, namely how the views and impacts of the implementation of employment policies for women with disabilities, especially those in Malang City. This study uses the qualitative approach of the Straussian version of the grounded theory method. Because Straussian tends to be more structured, it requires several rules and is complex so that it is open to various kinds of form the initial categories along with sub categories based on information extracted from the phenomenon.